Sea shadow - Farley, Terri (Farley, Terri. Phantom stallion, Wild Horse Island, 2008)
"When an earthquake sets off a tsunami on the shores of Wild Horse Island, the mustangs of Crimson Vale are chased by the waves and left stranded on a dangerous hilltop. Darby knows the lead mare, Medusa, will do anything to save her herd. But will she let the ranch hands bring her to safety?,or is it up to Darby to save Medusa and her band before they're lost forever?"--Cover, p. [4].